2012
DOI: 10.1017/s0029665112000791
|View full text |Cite
|
Sign up to set email alerts
|

The safety of oats in the dietary treatment of coeliac disease

Abstract: Coeliac disease is a permanent inflammatory disorder of the small bowel affecting approximately 1% of the population. The only effective treatment that exists is exclusion of gluten from the diet. The present paper aims to review the literature as to whether oats are safe to eat for people with coeliac disease. Much data exist on the restrictive nature that adhering to a gluten-free diet imposes on an individual. If oats could be eaten, this would help reduce the restrictive nature of the diet. This in turn co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…Although supported by data showing that exogenous (bovine) IAP could prevent NEC, this has not been demonstrated unequivocally. Celiac disease is a chronic inflammation of the small intestine caused by gluten from wheat and most other cereals . Depressed duodenal IAP protein expression and activity is especially marked in severe cases of celiac disease in young patients .…”
Section: Iap and Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although supported by data showing that exogenous (bovine) IAP could prevent NEC, this has not been demonstrated unequivocally. Celiac disease is a chronic inflammation of the small intestine caused by gluten from wheat and most other cereals . Depressed duodenal IAP protein expression and activity is especially marked in severe cases of celiac disease in young patients .…”
Section: Iap and Inflammatory Diseasesmentioning
confidence: 99%
“…Celiac disease is a chronic inflammation of the small intestine caused by gluten from wheat and most other cereals. 58 Depressed duodenal IAP protein expression and activity is especially marked in severe cases of celiac disease in young patients. 59,60 Importantly, tissue co-localization between IAP and LPS-receptor TLR-4 was reported.…”
Section: Possible Involvement Of An Iap Defect In Diseases Of the Smamentioning
confidence: 99%
“…They include oat, amaranth, acorn, chestnut, and teff flours. Oat flour is qualified as an alternative GF product, because for many years oats' safety in GFD was questioned (34). Oat-based products with Crossed Grain symbol have been available in Scandinavian countries for several years, but in countries like Poland only since 2013.…”
Section: The Content Of B-group Vitamins In Gf and Gluten Floursmentioning
confidence: 99%
“…Previous data showed that some CD patients developed enteropathy when oat was included in the diet [79,80]. The risk of enteropathy in CD patients may depend on oats varieties [66]. In contrast, the role and frequency of oats intolerance remain to be investigated in NCGS patients.…”
Section: Management Of Patients With Persistent Gastrointestinal Sympmentioning
confidence: 99%
“…GFD became popular in the last few years, and the global gluten-free market has increased substantially [65]. The liberalization of uncontaminated oat [66] and the use of pseudocereals as replacement for refined gluten-free flours have increased both the food variety and the nutrient content of the GFD [67,68].…”
Section: What Is Gluten-free Diet ?mentioning
confidence: 99%